(untitled) (Anwer Khan Modern Medical College Journal, 2014)
Public- Private Partnership (PPP) describes a government service or private business venture which is funded and operated through a partnership of government and one or more private sector companies. The term public refers to government including both central and local level state institutions. Defining private sector has become complicated due to the emergence of a large number of institutions called NGOs. The distinction of the private sector and NGOs is often blurred due to various sizes, functions and objectives of NGOs. The simplest way to distinguish between these two is: in case of profit private sector encompassing commercial enterprises of any size and for non-profit private including NGOs sector, which provides voluntary services. This review has grouped both the profit private sector, and non-profit NGOs under the term private sector. It also highlights PPP concept, importance, financing approaches as well as examples of model partnership in health sector in particular DOI: http://dx.doi.org/10.3329/akmmcj.v5i1.18843 Anwer Khan Modern Medical College Journal Vol. 5, No. 1: January 2014, Pages 42-45